(untitled) (Eurasian Journal of Ecology, 2024)
In the era of global climate challenges, Kazakhstan, like many countries around the world, faces the necessity of rethinking its approach to environmental policy. As part of international commitments, particularly the Paris Agreement, our country employs various regulatory tools aimed at reducing greenhouse gas emissions, setting ambitious yet realistic goals. In the context of these global efforts, Kazakhstan has identified key economic sectors for regulation within the emissions trading system at the legislative level. Within this market mechanism, priority areas requiring special attention and regulation include only energy and industry. However, the transport sector is also significant in terms of its impact on climate change, where the potential for emission reduction is also considerable. Given the substantial contribution of emissions from mobile sources to the total volume of national greenhouse gas emissions and the growing necessity to achieve global climate goals, there is an urgent need to integrate the transport sector into existing greenhouse gas emission regulatory mechanisms. This article explores the potential and prospects for including the transport sector of the Republic of Kazakhstan in the emissions trading system, specifically presenting the possibilities for regulating emissions from mobile sources, introducing an assessment approach, and constructing a proposed model for their measurement. Key words: greenhouse gases, carbon dioxide, transport sector, mobile sources, emissions trading system, carbon market